Preparation, Characterization, and H2S Sensing Performance of Sprayed Nanostructured SnO2 Thin Films. (26th June 2012) - Bari, R. H.; Khadayate, R. S.; Patil, S. B.; Bari, A. R.; Jain, G. H.; Patil, L. A.; Kale, B. B.
Abstract : Nanostructured SnO2 thin films were prepared by spraying tin chloride dihydrate onto the heated glass substrate at 250°C. The films were fired at 500°C. As-prepared thin films were studied using XRD and FESEM to know crystal structure and surface morphology. The average crystallite and grain size observed from XRD and FF-SEM was found to be less than 33 and 67 nm, respectively. The films sprayed for 30 min were observed to be most sensitive to H2 S at 250°C. The results are discussed and interpreted.